"My brothers have my back" : inside the November 1969 battle on the Vietnamese DMZ - Pepi, Lou (Jefferson, North Carolina : McFarland & Company, Inc., 2018)
In November 1969, what Time Magazine called the "largest battle of the year" took place less than two miles from the Vietnamese Demilitarized Zone. Three companies of Task Force 1-61 met 2,000-3,000 North Vietnamese. American forces fought for two days, inflicting heavy casualties and suffering eight killed. Late on November 12, it became evident that the American position could be overrun. Alpha Company was airlifted in darkness to reinforce a small hill in the jungle. Three hours later, well past midnight, the Americans were attacked by 1,500 NVA. There was a twist: A secret Vietcong document captured near Saigon urged intense action before November 14 in anticipation of the Vietnam War Moratorium Demonstrations set for November 15 in many cities in America. The Vietcong planned to inflict a stunning defeat in "an effort to get the fighting in step with the peace marchers." The author, a member of Alpha Company who rode in on the last helicopter, offers unique insights into the story of the men who fought those three days in 1969.
16. Chris Martin and the Americal DivisionEpilogue; Afterword by Clyde "Bud" Wagner; Appendix A: What They Are Doing Today; Appendix B: Awards Index; Appendix C: Valorous Unit Citation; Appendix D: Glossary; Appendix E: Communication Logs, 11-13 Nov 1969; Appendix F: The "Rules" of Engagement; Chapter Notes; Index
Online resource; title from PDF title page (EBSCO, viewed October 23, 2018).
eBooks on EBSCOhost
Keywords: Pepi, Lou; Vietnam War, 1961-1975 -- Campaigns; Vietnam War, 1961-1975 -- Personal narratives, American; Guerre du Viêt-nam, 1961-1975 -- Campagnes et batailles; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- Asia -- Southeast Asia; Military campaigns; 1961-1975; Electronic books; Autobiography; Personal Narrative; autobiographies (literary genre); Personal narratives; Autobiographies; Personal narratives -- American; Autobiographies; Personal narratives; Autobiographies; Récits personnels